Inseparability of Dairy Farming Technologies and Their Impacts on Milk Production Systems in Brazil - P. G. L. Lima; J. C. Damasceno; A. R. P. Simões; J. A. R. Borges; F. I. Bánkuti (Tropical Animal Science Journal, 2022)
Several studies have analyzed the impact of one technology on the productive performance of dairy systems. However, analyses that consider the impact of joint technologies are scarce. This study was aimed to analyze the inseparability of a set of technologies and their impacts on dairy farm performance. Questionnaires were applied on-site with 155 dairy farmers in Paraná State, Brazil. We collected 17 technological variables related to milk production and variables related to dairy farms’ production. Data analysis was performed in three steps: descriptive analysis, exploratory factor analysis (EFA), and multiple regression. Descriptive analysis was applied to characterize the sample, EFA was applied to generate factors related to the technological variables, and multiple regression was used to compare technological factors with productivity variables – farm performance. Four factors were defined: (i) Forage and farm structure, (ii) management, (iii) genetics, breeding strategies, and concentrate feeding, and (iv) animal health. The four factors significantly explained the differences in milk productivity between dairy farms. Technologies grouped under the factor of genetics were the most important in explaining milk yield per lactating cow, land productivity, and dairy herd reproductive efficiency.